Temporal changes in glucose metabolism reflect polarization in resident and monocyte-derived macrophages after myocardial infarction - Mouton, Alan J.; Aitken, Nikaela M.; Moak, Sydney P.; do Carmo, Jussara M.; da Silva, Alexandre A.; Omoto, Ana C. M.; Li, Xuan; Wang, Zhen; Schrimpe-Rutledge, Alexandra C.; Codreanu, Simona G.; Sherrod, Stacy D.; McLean, John A.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Metabolic reprogramming from glycolysis to the mitochondrial tricarboxylic acid (TCA) cycle and oxidative phosphorylation may mediate macrophage polarization from the pro-inflammatory M1 to the anti-inflammatory M2 phenotype. We hypothesized that changes in cardiac macrophage glucose metabolism would reflect polarization status after myocardial infarction (MI), ranging from the early inflammatory phase to the later wound healing phase. Methods MI was induced by permanent ligation of the left coronary artery in adult male C57BL/6J mice for 1 (D1), 3 (D3), or 7 (D7) days. Infarct macrophages were subjected to metabolic flux analysis or gene expression analysis. Monocyte versus resident cardiac macrophage metabolism was assessed using mice lacking the Ccr2 gene (CCR2 KO). Results By flow cytometry and RT-PCR, D1 macrophages exhibited an M1 phenotype while D7 macrophages exhibited an M2 phenotype. Macrophage glycolysis (extracellular acidification rate) was increased at D1 and D3, returning to basal levels at D7. Glucose oxidation (oxygen consumption rate) was decreased at D3, returning to basal levels at D7. At D1, glycolytic genes were elevated (Gapdh, Ldha, Pkm2), while TCA cycle genes were elevated at D3 (Idh1 and Idh2) and D7 (Pdha1, Idh1/2, Sdha/b). Surprisingly, Slc2a1 and Hk1/2 were increased at D7, as well as pentose phosphate pathway (PPP) genes (G6pdx, G6pd2, Pgd, Rpia, Taldo1), indicating increased PPP activity. Macrophages from CCR2 KO mice showed decreased glycolysis and increased glucose oxidation at D3, and decreases in Ldha and Pkm2 expression. Administration of dichloroacetate, a pyruvate dehydrogenase kinase inhibitor, robustly decreased pyruvate dehydrogenase phosphorylation in the non-infarcted remote zone, but did not affect macrophage phenotype or metabolism in the infarct zone. Discussion Our results indicate that changes in glucose metabolism and the PPP underlie macrophage polarization following MI, and that metabolic reprogramming is a key feature of monocyte-derived but not resident macrophages.